The Prose of Anastasia I. Tsvetaeva: Autobiographical Mythmaking - Ekaterina A. Esenina (Studia Litterarum)
Anastasia Tsvetayeva’s literary work can be largely defined as autobiographical. Her first pen probe, “Royal reflections,” is a philosophical essay where the author represents herself as a “theomachist” and the debunker of all moral values. Later, Tsvetaeva ventured into the genre of autobiographical novel, yet her novel may be called “autobiographical” only with some reservations. On the one hand, this work reflects real facts of the author’s life. On the other, the narrator, at some points, deliberately departs from truth, obscures and alters the facts, pursuing specific aims. The elements of autobiographical mythmak- ing may be found in the Memoirs of Anastasia Tsvetayeva that would be worthwhile to compare with the autobiographical prose of her elder sister Marina.